Selecting and managing partnerships in open innovation: evidence from a Malaysian family firm - Lim, Tien Shing (2023)
Innovation is the key driver for competitive advantage for businesses. It has been the main ingredient for economic growth of many major economies in the world. In the innovation practice, open innovation is identified as the new imperative for business success. Open innovation allows innovation to be more efficient with lower cost and shorter development time with the collaboration of external knowledge. For example, company like GE, Coca-Cola, Samsung and so forth have successfully employ open innovation to utilize external knowledge to create value. However, not all organizations are ready for open innovation. Organization flexibility with the appropriate structure and processes are required to capitalize open innovation. The absorptive capacity of the firm has to be developed internally so that it is enabled to accommodate open innovation strategy.